2016
DOI: 10.1002/1873-3468.12353
|View full text |Cite
|
Sign up to set email alerts
|

Impact of micro‐environmental changes on respiratory tract infections with intracellular bacteria

Abstract: Edited by Wilhelm JustCommunity-acquired pneumonia is caused by intra-and extracellular bacteria, with some of these bacteria also being linked to the pathogenesis of chronic lung diseases, including asthma and chronic obstructive pulmonary disease. Chlamydia pneumoniae is an obligate intracellular pathogen that is highly sensitive to micro-environmental conditions controlling both pathogen growth and host immune responses. The availability of nutrients, as well as changes in oxygen, pH and interferon-c levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 151 publications
1
27
0
Order By: Relevance
“…These authors also demonstrated that antibiotic usage disrupted this asymptomatic colonization and prevented asthmatic onset [27]. These findings support the hypothesis that colonization of the developing airway by certain microbes (both viral and bacterial) can significantly alter the airway architecture and overall immune function, influencing how the airway responds to a variety of insults [28]. These findings also suggest that antimicrobial agents may represent an effective therapeutic tool with the potential to curtail both the duration and severity of asthma exacerbations initiated by a variety of microbes and exposes the limitation of the hygiene hypothesis in this regard [26].…”
Section: The Human Microbiome and Asthma Risksupporting
confidence: 60%
“…These authors also demonstrated that antibiotic usage disrupted this asymptomatic colonization and prevented asthmatic onset [27]. These findings support the hypothesis that colonization of the developing airway by certain microbes (both viral and bacterial) can significantly alter the airway architecture and overall immune function, influencing how the airway responds to a variety of insults [28]. These findings also suggest that antimicrobial agents may represent an effective therapeutic tool with the potential to curtail both the duration and severity of asthma exacerbations initiated by a variety of microbes and exposes the limitation of the hygiene hypothesis in this regard [26].…”
Section: The Human Microbiome and Asthma Risksupporting
confidence: 60%
“…Differences among adult asthmatics have also been demonstrated under specific circumstances such as pregnancy [30]. These findings point out the possibility of impaired cytokine responses under determined factors that can interfere with asthma pathogenesis and C. pneumoniae infection [31].…”
Section: Discussionmentioning
confidence: 74%
“…Over the past two decades, molecular techniques, including those targeting the variable regions of the bacterial 16S ribosomal RNA (16S rRNA) gene, next‐generation sequencing, and metagenomic analyses, have changed our understanding of the human microbiome, including the respiratory microbiome, in health and disease. At each body habitat, the microbiome is believed to have complex relationships, both in the dynamics of its core and satellite organisms, and with its host, where it has potential interactions with the developing immune system and regulation of the inflammatory response …”
Section: Introductionmentioning
confidence: 99%